Unlocking the molecular mechanisms of antipsychotics – a new frontier for discovery (Swiss Medical Weekly, 2016)
Despite the use of antipsychotics to treat schizophrenia for the last several decades, little was understood about their molecular mechanisms of action. In this review, we discuss recent studies that have helped elucidate mechanisms of action of antipsychotics and their potential interplay with genetic, metabolomic, proteomic, and other cellular process-related discoveries in schizophrenia pathology. We also highlight genes that have been identified in multiple studies in both schizophrenia patients and in antipsychotic action that are related to glucose and cellular metabolism, the cytoskeleton, protein synthesis, cell adhesion and synaptic activity. Though some questions of antipsychotic mechanisms of action, such as primary versus off-target effects, remain, the recent gains in understanding how to treat schizophrenia at the molecular level are promising. We propose that these recent insights provide a new and more complete landscape for drug discovery and patient biomarker development.